Administration of School Administrators Based on the Four Principles of Sangahavatthu under Rayong Primary Educational Service Area Office 1 - พิมพ์วงศ์สัตย์, ณัฐวิโรจน์; รักษนคร, กุลจิรา; คงเที่ยง, สมศักดิ์; พรหมน้ำฉ่า, พรธิวา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to study and compare the opinions of teachers regarding the administration of school administrators based on the Four Principles of Social Harmony (Sanghahavattu 4) in schools under the Rayong Primary Educational Service Area Office 1. The sample group was determined using Taro Yamane's (1973) model, consisting of 340 teachers. The research instrument was a 5-level rating scale questionnaire with an Index of Content Validity (IOC) between 0.80-1.00 and a reliability coefficient of .92. Data were analyzed using descriptive statistics including frequency, percentage, mean, standard deviation, t-test, and F-test, as well as content analysis.            The research findings revealed that• Teachers' opinions regarding the administration of school administrators based on the Four Principles of Social Harmony (Sanghahavattu 4) in schools under the Rayong Primary Educational Service Area Office 1 were generally at a high level, both overall and in individual aspects. When considering each aspect individually, the aspect with the highest average score was Samanattata (equality), followed by Atthacariya (beneficial conduct), also at a high level, and the aspect with the lowest average score was Piyavaca (kind speech), also at a high level.• Comparing different genders and educational levels, the level of school administrators' performance based on the Four Principles of Social Harmony (Sanghahavattu 4) in schools under the Rayong Primary Educational Service Area Office 1, both overall and in specific aspects, did not differ significantly, except for school size, which differed significantly at the .01 statistical significance level.